Discussion of the classification of pediatric drug clinical trials in children's hospitals in China - Yang, Yong; Jiang, Rui; Bai, Gengliang; Liu, Qingqing; Chen, Yongfa (Frontiers in Medicine, 2024)
Objectives This study aimed to gain insights into pediatric clinical trials conducted in children's hospitals in China and provide valuable references for the development of children's hospitals and the research and development of pediatric drugs. Methods A comprehensive search was performed on the Chinese Clinical Trial Registry (Chi CTR) and ChinaDrugTrials.org.cn to collect information on all clinical trials involving subjects under 18 years, including those conducted in children's hospitals. The retrieval period was extended until 31 December 2022. Results A total of 459 pediatric clinical trials were collected, comprising 299 from Chi CTR and 160 from the Drug Clinical Trial Registration and Information Publicity Platform (Information Platform). Post-marketing drug studies and phase III clinical trials accounted for the majority of research stages. These trials covered a wide range of diseases/systems, with a particular focus on respiratory system disorders, tumors, endocrine disorders, and nutritional or metabolic diseases. Chemical drugs constituted the most extensively studied category, while traditional Chinese medicine/natural drugs received comparatively less attention. Clinical trial activities were primarily geographically focused on the eastern coastal regions of China, with multicenter trials being the most predominant. Ethics committee approval was obtained for 427 studies. Conclusion The pediatric clinical trials conducted by children's hospitals in China have shown an overall upward trend; however, there is limited research focusing on traditional Chinese medicine, along with significant regional and institutional imbalances. Furthermore, there is still room for improvement regarding ethical review processes. It is recommended that children's hospitals enhance their scientific research capabilities while optimizing resource allocation to meet medical service demands effectively. Additionally, fostering more research-focused children's hospitals will contribute to the high-quality development of children's health in China.